Epiphytic algae on mosses from Northern Victoria Land (Antarctica) - ALFINITO, Silvia; FUMANTI, Bruno; P. Cavacini (Schweizerbart science publisher, 1998)
Six different sites of Northern Victoria Land (Antarctica) in which algal growth was present on moss turfs and cushions were investigated. A total of 38 algal taxa were identified: 24 Cyanophyceae, 2 Xanthophyta, 6 Bacillariophyta and 6 Chlorophyta. Cyanophyceae were dominant in all the samples. The most frequent species were Phormidium frigidum and Nostoc commune. Our observations and a comparision with the literature show that there does not seem to exist a characteristic epiphytic algal flora on mosses, at least not for Continental Antarctica. In fact, all species identified were simultaneously present and also found in other aquatic and subaerial environments. Their presence on mosses seems to depend exclusively on their capacity to reach the gametophytes, either directly from the soil or transported wind or birds.